Impact of varying cognitive resources on memory recall - Zhang, Ruo-Chong (2023)
Our ability to pay attention to and remember relevant information while ignoring irrelevant information is limited by the cognitive resources we have. Switching between learning words and performing a difficult secondary task can increase cognitive load, deplete resources, and impair performance on the primary task, learning. However, there are instances where interleaving to-be-remembered information and a secondary task improves memory recall at a delay. In this thesis, I report a series of studies and literature reviews examining word-lists learning and recall when presented interleaved with a cognitively demanding secondary task. In the first strand, I varied the difficulty of the secondary task to examine how cognitive load affect the number of recall and how items were organised during recall among young and older adults. In the second strand, I examined approaches that potentially enhance cognitive resources, including noninvasive brain stimulation and caffeine, on memory. The results converge on the dynamic, fluid nature of cognitive resources: firstly, resources do not decrease linearly with increased task difficulty and cognitive load; instead, recall depends on the ongoing resources distribution between remembering words and monitoring secondary task performances. Secondly, resources may be replenished or augmented with endogenous and exogenous modulation. These findings set the foundation for theoretical and measurement advancements for cognitive resources.